Elioraea tepida, sp. nov., a Moderately Thermophilic Aerobic Anoxygenic Phototrophic Bacterium Isolated from the Mat Community of an Alkaline Siliceous Hot Spring in Yellowstone National Park, WY, USA - Mohit Kumar Saini; Shohei Yoshida; Aswathy Sebastian; Eri Hara; Hideyuki Tamaki; Nathan T. Soulier; Istvan Albert; Satoshi Hanada; Marcus Tank; Donald A. Bryant (Microorganisms, 2021)
Strain MS-P2T was isolated from microbial mats associated with Mushroom Spring, an alkaline siliceous hot spring in Yellowstone National Park, WY, USA. The isolate grows chemoheterotrophically by oxygen-dependent respiration, and light stimulates photoheterotrophic growth under strictly oxic conditions. Strain MS-P2T synthesizes bacteriochlorophyll a and the carotenoid spirilloxanthin. However, photoautotrophic growth did not occur under oxic or anoxic conditions, suggesting that this strain should be classified as an aerobic anoxygenic phototrophic bacterium. Strain MS-P2T cells are motile, curved rods about 0.5 to 1.0 μm wide and 1.0 to 1.5 μm long. The optimum growth temperature is 45–50 °C, and the optimum pH for growth is circum-neutral (pH 7.0–7.5). Sequence analysis of the 16S rRNA gene revealed that strain MS-P2T is closely related to Elioraea species, members of the class Alphaproteobacteria, with a sequence identity of 96.58 to 98%. The genome of strain MS-P2T is a single circular DNA molecule of 3,367,643 bp with a mol% guanine-plus-cytosine content of 70.6%. Based on phylogenetic, physiological, biochemical, and genomic characteristics, we propose this bacteriochlorophyll a-containing isolate is a new species belonging to the genus Elioraea, with the suggested name Elioraeatepida. The type-strain is strain MS-P2T (= JCM33060T = ATCC TSD-174T).